Penggunaan Metode Jarimatika Untuk Meningkatkan Aktivitasdan Hasil Belajarmatematika Materi Perkalian Pada Siswa Kelas IIA SD Muhammadiyah 8 Jagalan Surakarta Tahun Ajaran 2015/2016 - DWIYANTO, ANDI, Drs. Saring Marsudi, SH. M.Pd (2016)
ABSTRACT Andi Dwiyanto/A510120073. FINGERMATH USE METHOD TO INCREASE ACTIVITY AND RESULTS OF MATHEMATICS LEARNING MATERIALS IN CLASS IIA MULTIPLICATION ELEMENTARY SCHOOL MUHAMMADIYAHSURAKARTA 8 JAGALAN 2015/2016 ACADEMIC YEAR. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. April, 2016. This study aims to improve the activity and learning outcomes in Mathematics. The subjects of research that teachers and students of class IIA Muhammadiyah 8 Jagalan Elementary School Year 2015/2016 a number of 22 students. This research is a class act. Research was conducted during two cycles. Collecting data through interviews, observation, testing and documentation. As for the validity of the data using triangulation and triangulation methods. Data analysis process includes planning, data reduction, data presentation, and conclusion. The results showed an increase of activity and learning outcomes. Improvement of learning activities can be shown on the indicators which include: 1) Reading increased from 51, 10% (pre-cycle), 69.32% (first cycle), 84.09% (second cycle). 2) Listening increased from 53.40% (pre-cycle), 71.59% (first cycle), 82.95% (second cycle). 3) Ask a question increased from 52.3% (pre-cycle), 73.86% (first cycle), 82.95% (second cycle). 4) Answer questions increased from 59.1% (pre-cycle), 72.73% (first cycle), 89.77% (second cycle). 5) Solve problems increased from 53.4% (pre-cycle), 68.18% (first cycle), 80.68% (second cycle). While the learning outcomes increased from 40.91% before treatment (pre-cycle), Cycle 1 (77.27%), cycle 2 (95.45%). The conclusion of this study is through the use of methods Jarimatika can increase the activity and results of learning mathematics in grade IIA Muhammadiyah 8 Jagalan Elementary School Year 2015/2016. Keywords: Fingermath methods, learning activities, learning outcomes.